2019
DOI: 10.2147/opth.s219742
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Outcomes Of Descemet Membrane Endothelial Keratoplasty Using The Bonfadini-Todd Injector For Graft Insertion</p>

Abstract: PurposeTo evaluate the clinical outcomes of using an Alcon intraocular lens (IOL) B cartridge for graft insertion during Descemet membrane endothelial keratoplasty (DMEK).Patients and methodsWe retrospectively reviewed medical charts of patients who underwent DMEK using the Bonfadini-Todd injector, composed of an Alcon IOL B cartridge connected to plastic tubing and a syringe, for graft insertion between May 2016 and August 2018. Patient demographics, diagnoses, donor information, visual acuity, intraocular pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…[ 30 ] and Ighani et al . [ 29 ] studies had better and worse preoperative BSCVA, respectively (p<0.0001 and p = 0.09). These baseline differences are important because Chaurasia et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[ 30 ] and Ighani et al . [ 29 ] studies had better and worse preoperative BSCVA, respectively (p<0.0001 and p = 0.09). These baseline differences are important because Chaurasia et al .…”
Section: Discussionmentioning
confidence: 97%
“…A small study by Ighani et al . also did not observe visual acuity differences between triple-DMEK ( n = 16) and pseudophakic-DMEK ( n = 8) at a mean follow-up duration of 13 months (range, 3–26) months [ 29 ]. These findings are also consistent with an earlier case-series study by Laaser et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, it should facilitate the loading of the graft, cause minimal cell loss/damage to the endothelium, and preserve the AC volume upon insertion. Surgeons may choose from a range of different insertion devices available commercially [50]. In our experience, we found that it was easier to start with glass injectors such as the Geuder glass tube (Geuder AG, Heidelberg, Germany).…”
Section: Dmek Graft Staining Loading and Insertionmentioning
confidence: 99%
“…We note that Descemet membrane contains elastin and its elastic properties may contribute to the scrolling characteristics of the graft after stripping. [89,90,91,92] We postulate that this may be influenced by the speed of stripping of the Descemet's from the stroma during DMEK graft preparation secondary to the effect and duration of tension on the elastic recoil of the tissue. To our knowledge, no studies have been performed to investigate the effect of the stripping speed on the scrolling behaviour and final graft scroll width resulting in preparation for subsequent DMEK.…”
Section: Introductionmentioning
confidence: 99%